Respuesta :
The components of the summation process are the addends which are the numbers added together and the sum which is the result. In this item, in order to determine the other addend, we have to subtract the given addend from the given sum,
(10a²b² - 8a²b + 6ab² - 4ab + 2) - (-5a²b² + 12a²b - 5)
Grouping similar terms,
(10a²b²) - (-5a²b²) = 15a²b²
(-8a²b) - (12a²b) = -20a²b
(6ab²) - 0 = 6ab²
(-4ab) - 0 = -4ab
(2) - (-5) = 7
Combining the terms,
= 15a²b² - 20a²b + 6ab² - 4ab + 7
Thus, the answer is the first choice.
(10a²b² - 8a²b + 6ab² - 4ab + 2) - (-5a²b² + 12a²b - 5)
Grouping similar terms,
(10a²b²) - (-5a²b²) = 15a²b²
(-8a²b) - (12a²b) = -20a²b
(6ab²) - 0 = 6ab²
(-4ab) - 0 = -4ab
(2) - (-5) = 7
Combining the terms,
= 15a²b² - 20a²b + 6ab² - 4ab + 7
Thus, the answer is the first choice.